The Evaluation of Low-Cost Apartment Building Lampung University (Rusunawa Building) Using Greenship Rating Tools for Existing Buildings - Kustiani, Ika; Isneini, M; Girinandi, I; Aminudin, KM; Surahman, R; Aini , N; Mardhotillah , AN; Widyawati, Ratna (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2024)
The assessment of the green building at the Rusunawa Lampung University was conducted using the Greenship Rating Tools for Existing Building Version 1.1. Measurements were carried out to examine the overall sub-criteria of each greenship assessment category. The greenship rating tools for existing buildings version 1.1 are quite complex, as there are 6 (six) feasibility tests and sub-criteria. Based on field measurements and analysis of the green building assessment criteria using the greenship existing building rating tools version 1.1 at the Rusunawa Lampung University, as there used rating score of 17 points. The final result, the Rusunawa Building Lampung University does not have a rating for the Green Building criteria. To achieve a minimum bronze rating, and an assessment of the greenship assessment categories, the parties felt necessary to obtain recommendations for the improvements according to the assessment matrix that can enhance the Green Building rating for Rusunawa Lampung University.